Type II Half Logistic Kumaraswamy Distribution with Applications. (1st August 2020) - ZeinEldin, Ramadan A.; Haq, Muhammad Ahsan ul; Hashmi, Sharqa; Elsehety, Mahmoud; Elgarhy, M.
Abstract : In this paper, a new distribution with a unit interval named type II half logistic Kumaraswamy (TIIHLKw) distribution is proposed. Its density and distribution functions are presented using alternate expressions. This distribution is obtained by adding an extra parameter in the existing model to rise its ability fitting complex data sets. Some important statistical properties of TIIHLKw distribution are derived. The estimation of the parameters is obtained by numerous well-recognized approaches and simulation study confirmed the efficiencies of estimates such obtained. We apply the related model to practical datasets, and it is concluded that the proposed model is the best by model selection criteria than other competitive models.